A Study of Tense, Aspect and Modality in The Economists’ Warnings by The Financial Times - AKPACA, SERVAIS MARTIAL (My University, 2014)
Translation is the transfer of meaning from a source language to a target language. This transfer is done through sentences. Sentence meaning is conveyed through words, tenses, aspects and modals. This paper focuses on tenses, aspects and modals as elements of sentence semantics. The choice of these elements in the target language is complex most of the time because there is no perfect fit between them in two languages.
Keywords: Tense; aspect; modality; translation; sentence semantics